MEAT CONTENT OF PORTUNUS PELAGICUS WITH SOME OBSERVATIONS ON LUNAR PERIODICITY IN RELATION TO ABUNDANCE, WEIGHT AND MOULTING - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
Study shows that the male orabs of Portunus pelagicus contain more meat than feamles. Crab catches were relatively good during the new moon phase than during the full moon phase. The variation in the weight of P. pelagicus during the two moon phases is much less. The recently-moulted crabs in the commercial catches were relatively more during the new moon phase than in full moon period.